Determination of Physical Properties of FYM for the Development of FYM Shredder cum Spreader - Vinayak, M.; Ramana, C.; Haribabu, B.; Reddy, K. Madusudhana (International Journal of Bio-resource and Stress Management, 2022)
A research work was undertaken at the Department Agricultural Engineering, Regional Agricultural Research Station, Tirupathi, Andhra Pradesh, India during 2020 to study the physical properties of FYM for the designing the tractor mounted FYM spreader. Application of FYM increases the soil fertility. FYM contained almost all essential nutrients required for soil. The important FYM physical properties like moisture content, bulk density, angle of repose, coefficient of friction are required for development of FYM shredder cum spreader. The FYM is heterogeneous mixture and its moisture content varies at different depths stored in manure pits for measuring the physical characteristics, three depths of manure pits viz., 0-20, 20-40, 40-60 cm collected and were used. Designing The physical properties found in FYM like moisture content, bulk density, angle of repose and coefficient of friction and sieve analysis of FYM at different depth of manure pit were 61% db 20% wb,0.650 gcm-3,71.03 and 34° respectively. The initial bulk density form before the operation 0.650 g cm-3andclod size is major at 70% at 50 mm screen opening after shredder operation the bulk density decreases 0.250 g cm-3 and 40% of FYM retained less than 10 mm sieves at the shredder speed is 255 RPM. The developed shredder was successful in reducing 70% aggregation size from more than 50 mm-less than10 mm sieve opening which is desirable form of FYM application.